The Effects of Organizational Hierarchy, Culture and Organizational Climate on Organizational Commitment in Banking Sector of Azerbaijan - Mammadova, Fidan (ADA University, 2022)
Organizational commitment enables employees to form an identity unity with the organization, establish long-term relationships, adopt the goals of the organization and work with enthusiasm, and encourage employees to exhibit the desired behaviors towards the goals of the organization. The high level of organizational commitment of the employees leads to many positive results such as the decrease in the rate of turnover in the organization, the increase in the performance of the employees, and the greater participation of the employees in the beneficial activities within the organization. Considering direct contributions of banking sector to the country's economy, the efficiency, productivity and profitability of the banking sector and employees in the banking sector is a very important issue for Azerbaijan, and in this context, it is thought that it is very important to examine the Azerbaijani banking sector in terms of organizational culture, climate, and commitment in the research. The subject of the thesis is determined as the impact of organizational hierarchy culture and organizational climate on organizational commitment in employees. Based on various studies on organizational commitment, within the scope of this study, the concept of organizational commitment was discussed in three sub-dimensions as an emotional, continuance, and normative commitment within the framework of Meyer and Allen's (1997) approach. The hypotheses developed later in the research were examined by simple linear regression analysis. Within the framework of the hypotheses, first of all, the effects of organizational culture and then organizational climate on organizational commitment and its sub-dimensions are discussed. As a data collection tool, survey application was carried out between 01/03/2022 – 20/04/2022. The survey application was filled in digitally distributing the questionnaire to the individuals employed in the Banking Sector in Azerbaijan. 6 hypotheses out 7 were justified as a result of bivariate regression analysis, and it was concluded that organizational culture perceptions of the employees are "strong", organizational climate perceptions are "positive" and organizational commitment levels are "high". The type of commitment that employees have the most is continuance commitment.
Keywords: Organizational commitment.; Organizational culture.; Hierarchy culture.; Organizational climate.; Banking sector.; Business